Sequential extraction and characterization of the organic layer on sandstone reservoir rock surface. (15th September 2020) - Wicking, Chrissie; Tessarolo, Nathalia; Savvoulidi, Magdalena; Crouch, Jonathan; Collins, Ian; Couves, John; Kot, Emilia; Banks, Nicole; Hodges, Mike; Zeng, Huang
Graphical abstract: Highlights: The organic materials covering reservoir rock surface can sequentially extracted. The organics on rock surface are dramatically different from those in the oil. Representative model compounds for the organic on rock surface are proposed. These organics might be in a layered structure on the rock surface. Understanding of "organic layer" is important for oil exploration and production. Abstract: Reservoir rocks are partially coated by certain organic molecules (organics) which could have a strong impact on the wettability of the rock and, subsequently, oil recovery. It is important to understand the detailed chemical composition of this "organic layer" in order to design better oil/gas recovery methods. Herein, we report the sequential extraction and the qualitative characterization of the organics from reservoir rocks based on high resolution mass spectrometry (HRMS). The composition of these organics is significantly different from those in the bulk oil. The methodology and findings of this study will be useful for the identification of molecular markers important for enhanced oil recovery.